The Effectiveness of Teaching English Vocabulary Using Dictionary Online Media in STTR Cepu in Academic Year of 2020-2021 - Helmi Gunawan (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2021)
The Covid-19 pandemic, apart from providing a bad experience, can also make someone challenged and offer to develop learning but in Engineering English lectures. At first the learning was carried out face-to-face, this time it was carried out boldly. Vocabulary is a basic and important knowledge in Mastering English. One of the vocabulary learning strategies during the pandemic is through online media. This research was conducted in order to determine the effectiveness of vocabulary learning by using an online dictionary for Mechanical Engineering Students STTR Cepu. This study used a descriptive approach. There are 30 students as respondents. Based on the questionnaire and strongly agree by 43.3%, agree by 46.7% say disagree and strongly agree. So that it can be said that the effectiveness of learning vocabulary using online dictionaries is weak in mechanical engineering students at STTR Cepu.